Risks of Web projects - E. Yu. Dorokhina (Путеводитель предпринимателя, 2020)
The paper presents shows the place and role of web projects in the system of projects related to the use of information technologies. The low efficiency of it projects and web projects, in particular, makes it necessary to develop new approaches to management. The most important specific risks of web projects and their sources are analyzed. The classification of web project risks is proposed.